The Role of Logos in Conveying Organizational Personality: A Case Study of the Ministry of Tourism and Creative Economy of the Republic of Indonesia - Ilham Saputra; Morissan Morissan (Eastasouth Institute, 2026)
Logo changes in public institutions are not only related to aesthetic aspects but also carry strategic meanings, cultural identity, and organizational representation. This study aims to analyze employee perceptions of the new logo of the Ministry of Tourism and Creative Economy (Kemenparekraf) and examine the role of visual identity as a representation of organizational identity. The research employed a mixed-methods approach with data collection through questionnaires (N=104) and in-depth interviews. Quantitative data were analyzed using reliability tests, descriptive statistics, normality tests, Pearson correlation, and ANOVA with the help of SPSS, while qualitative data were analyzed thematically. The results indicated that the research instrument was reliable (Cronbach's Alpha = 0.934), employees' perceptions of the new logo were generally positive (X mean = 24.19; Y mean = 28.85), and there was a very strong positive correlation between visual identity perceptions and organizational identity representation (r = 0.750; p < 0.001). The ANOVA analysis also revealed significant differences across respondent groups (F = 7.838; p < 0.001). Qualitative findings emphasize that the logo change was driven by rebranding needs, visual continuity from the previous logo, and the demands of creative economic globalization. This study concludes that the new Kemenparekraf logo serves as a strategic visual instrument that not only builds organizational image but also strengthens internal organizational support.